Presence of foodborne pathogens, extended-spectrum beta-lactamase -producing Enterobacteriaceae, and methicillin-resistant Staphylococcus aureus in slaughtered reindeer in northern Finland and Norway - Laaksonen, Sauli; Oksanen, Antti; Julmi, Jerome; Zweifel, Claudio; Fredriksson-Ahomaa, Maria; Stephan, Roger (Acta Veterinaria Scandinavica, 2017)
Background: Various food-producing animals were recognized in recent years as healthy carriers of bacterial pathogens causing human illness. In northern Fennoscandia, the husbandry of semi-domesticated reindeer (Rangifer tarandus tarandus) is a traditional livelihood and meat is the main product. This study determined the presence of selected foodborne pathogens, methicillin-resistant Staphylococcus aureus (MRSA), and extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae in healthy semi-domesticated reindeer at slaughter in northern Finland and Norway. Results: All 470 reindeer fecal samples tested negative for Salmonella spp., whereas L. monocytogenes was detected in 3%, Yersinia spp. in 10%, and Shiga toxins genes (stx1 and/or stx2) in 33% of the samples. Listeria monocytogenes isolates belonged to the serotype 1/2a (14/15) and 4b, Yersinia spp. were identified mainly as Y. kristensenii (30/46) and Y. enterocolitica (8/46), and stx2 predominated among the Shiga toxin genes (stx2 alone or in combination with stx1 was found in 25% of the samples). With regard to the frequency and distribution of stx1/stx2, striking differences were evident among the 10 different areas of origin. Hence, reindeer could constitute a reservoir for Shiga toxin-producing E. coli (STEC), but strain isolation and characterization is required for verification purposes and to assess the potential human pathogenicity of strains. On the other hand, the favorable antibiotic resistance profiles (only 5% of 95 E. coli isolates were resistant to one or more of the tested antibiotics) and the absence of MRSA and ESBL-producing Enterobacteriaceae (when applying selective methods) suggest only a limited risk of transmission to humans. Conclusions: Healthy semi-domesticated reindeer in northern Finland and Norway can be carriers of certain bacterial foodborne pathogens. Strict compliance with good hygiene practices during any step of slaughter (in particular during dehiding and evisceration) is therefore of central importance to ...